Mirmecofilia e mirmecofagia de Attacobius sp. (Araneae: Corinnidae) sobre Solenopsis saevissima (Hymenoptera : Myrmicinae) - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Some animals known as myrmecophiles evolved strategies of mimicry by biosynthesis or camouflage. In the municipality of Morrinhos, southern region of the state of Goiás, a new species of spider of the genus Attacobius associated to the colonies of Solenopsis saevissima was discovered. This study aims to determine the mechanisms and adaptations that allow the mimicry of the Attacobius sp. with S. saevissima. Five colonies of S. saevissima containing Attacobius sp. were collected in the field, identified and kept alive inside plastic trays with food and water for conducting behavioral and predation tests. Attacobius sp. was found in 42% of the 12 collection sites and on average 47% of the colonies in the places where the spider occurred. There was no predation on adults (workers and sexual castes). Although not quantified, the spiders consumed eggs via kleptoparasitism. Each spider consumed on average five larvae or three pupae per day. Considering that the average spider abundance was approximately seven spiders per colony (range 1-23), an average impact of 28 larvae or pupae per day on the colony is predicted. Analysis of cuticle hydrocarbons (HCCs) of Attacobius sp. and S. saevissima showed no significant chemical difference between workers and spiders (PERMANOVA). The constant persecution and contact with the workers and the grooming behavior indicate the chemical camouflage of the spiders.
Myrmecophily and myrmecophagy of Attacobius sp. (Araneae: Corinnidae) on Solenopsis saevissima (Hymenoptera : Myrmicinae)
Keywords: Mimetism; Lava-pés; Hidrocarbonetos cuticulares; Cleptoparasitismo; Inquilinismo; Chemical mimicry; Fire ant; Cuticular hydrocarbon; Kleptoparasitism; Inquilinism; CIENCIAS BIOLOGICAS